[Rica and the Virgin of Guadalupe mural] - Cayetano Contreras, Jr.::::::photographer::: (2005)
Description supplied by photographer: "Una foto de mi amigo Rica en mi casa, posando en frente del mural de la Virgen de Guadalupe que mi tío Rojo pintó. Es especial porque fue pintada por mi tío que murió." Translation of description: "A photo of my friend Rica at my house posing in front of the mural of the Virgin of Guadalupe that was painted by my uncle Rojo. It is special to me because he painted it and he died a few years ago."